A clinical review of robotic navigation in total knee arthroplasty: historical systems to modern design. Issue 4 (April 2021) - Siddiqi, Ahmed; Horan, Timothy; Molloy, Robert M.; Bloomfield, Michael R.; Patel, Preetesh D.; Piuzzi, Nicolas S.
Abstract : Robotic-assisted total knee arthroplasty (RA-TKA) has shown improved reproducibility and precision in mechanical alignment restoration, with improvement in early functional outcomes and 90-day episode of care cost savings compared to conventional TKA in some studies. However, its value is still to be determined. Current studies of RA-TKA systems are limited by short-term follow-up and significant heterogeneity of the available systems. In today's paradigm shift towards an increased emphasis on quality of care while curtailing costs, providing value-based care is the primary goal for healthcare systems and clinicians. As robotic technology continues to develop, longer-term studies evaluating implant survivorship and complications will determine whether the initial capital is offset by improved outcomes. Future studies will have to determine the value of RA-TKA based on longer-term survivorships, patient-reported outcome measures, functional outcomes, and patient satisfaction measures. Cite this article: EFORT Open Rev 2021;6:252-269. DOI: 10.1302/2058-5241.6.200071